Home care enteral feeding 10th Nestlé Nutrition Workshop, Berlin-Potsdam, June 2004 ; new insights into complex nutrient-health interactions - Lochs, Herbert; Thomas, David R. (Nestlé nutrition workshop series. Clinical & performance programme, 2005)
The poor nutritional status of the elderly living at home is a widespread problem. Many have energy and nutrient intakes below international standards. Almost one in five community-dwelling older adults lives on less than 1,000 kcal/day. The causes are dependent on sociological, psychological, and physiological factors. Significant reductions in energy intake accompany medical illness, and thus a causal connection between the role of proinflammatory cytokines and illness-induced undernutrition has been alleged.This challenge has now been addressed and analyzed by an international panel of leading experts at the 10th Nestlé Nutrition Workshop in Berlin. Their work has brought the epidemiology, pathophysiology and the role of cytokines and immunomodulation in the management of undernutrition to the center of scholar attention. This book is a synthesis of state-of-the-art knowledge and expertise in this field of research and will be of high value for all medical and healthcare professionals who wish to gain insight into the complex interactions between nutrient intake and health